Analisis Kesulitan Belajar Dalam Menyimak Pada Pembelajaran Bahasa Indonesia Kelas V SDN 19 Tanjung Tengang - Lepiana, Lepiana; Mardiana, Mardiana; Tirsa, Aprima (STKIP Melawi, 2025)
Abstract: The research is based on students' difficulties in listening. The aim of the study was to find out the learning difficulties in listening to lessons in Indonesian language learning for Class V Elementary School 19 Tanjung Tengang. The research method uses qualitative research with an analytic descriptive approach. the subjects in this study were class teachers and fifth grade students. The object of research was learning difficulties in listening to Indonesian language learning. The research instrument uses interview sheets and observation sheets. Data collection techniques using observation, interviews and documentation. Checking the validity of the data using triangulation of sources and techniques. The results of the study revealed that the difficulties experienced by students in listening to Indonesian language lessons in fifth grade students at Class V Elementary School 19 Tanjung Tengang were that students had difficulties in focusing attention or concentrating on learning to listen to the lessons conveyed by the teacher. Difficulty in concentrating on listening can interfere with students' fluency in understanding the content of the listening. While the factors that hinder students from listening are attitude factors and environmental factors. Attitude factors such as there are students who are busy playing and talking with their peers during the learning process. While environmental factors are learning atmosphere that is less conducive.Keywords: Difficulty, Learning, Listening.Â Abstrak: Penelitian didasari oleh kesulitan siswa dalam menyimak. Tujuan penelitian untuk mengetahui kesulitan belajar dalam menyimak pembelajaran pada pembelajaran Bahasa Indonesia kelas V SD Negeri 19 Tanjung Tengang. Metode penelitian menggunakan penelitian kualitatif dengan pendekatan deskriptif analitik. subjek dalam penelitian ini guru kelas dan siswa kelas V. Objek penelitian adalah kesulitan belajar dalam menyimak pada pembelajaran Bahasa Indonesia. Instrumen penelitian menggunakan lembar wawancara dan lembar observasi. Teknik pengumpulan data menggunakan observasi, wawancara dan dokumentasi. Pengecekan keabsahan data menggunakan triangulasi sumber dan teknik. Hasil penelitian diketahui bahwa kesulitan yang dialami siswa dalam menyimak pembelajaran Bahasa Indonesia pada siswa kelas V di SD Negeri 19 Tanjung Tengang adalah siswa kesulitan dalam memusatkan perhatian atau konsentrasi belajar untuk menyimak pembelajaran yang disampaikan oleh guru. Kesulitan dalam memusatkan perhatian untuk menyimak, dapat mengganggu kelancaran siswa dalam memahami isi simakan. Sedangkan faktor yang menghambat siswa menyimak adalah faktor sikap dan faktor lingkungan. Faktor sikap seperti ada siswa yang sibuk bermain dan berbicara dengan teman sebangkunya pada saat proses pembelajaran. Sedangkan faktor lingkungan adalah suasana belajar yang kurang kondusif.Kata Kunci: Kesulitan, Belajar, Menyimak.